Material selection and design of shell and tube heat exchanger for thermos-syphon steam generator. Issue 1 (March 2021) - Solke, Nitin S; Sur, Anirban; Sapre, Mandar
Abstract: Pure steam generated by conventional boiler is not devoid of chemical additives, rust or other undesirable materials and fails to meet essential quality of steam needed for pharmaceutical and health care process industries for WFI(Water for Injection), sterilization of medical equipment and clean room humidification on account of the limitations in achieving desired standards needed by the qualities of ideal pure steam such as pH value, conductivity, bacteria count etc. as prescribed by the International Society of Pharmaceutical Engineers (ISPE). Dry and pure steam is produced by 'pure steam generators' using purification process of the plant steam and doesn't contain any liquid droplets, any anti scaling additives and corrosion inhibitors. - Thermo siphon type Pure Steam Generator has been chosen in the present project for its extremely good heat transfer performance at low temperature differences, less sensitivity to large changes in process condition and more stable operation. In this paper design of the heat exchanger for generation of pure steam has been discussed. Here shell and tube type heat exchanger has been selected due to its flexibility of design, which allows wide range of pressures and temperatures. Standards laid out in ASME BPE for selection of material, CGMP and TEMA for design and manufacturing methods are followed for efficient and safe steam generation. Parameters given by the industry to meet customers' requirements have been considered while designing the HE, its accessories, piping, valves and instruments. Thermal design of the two phase shell and tube heat exchanger has been done manually and validated using HTRI suite. The mean % error between HTRI results and manual results is 12.05%.